Sistem Informasi Manajemen Pelanggan (Simapel) Internet Service Provider Murni Jaya Berbasis Website: Studi Kasus: BUMDes Murni Jaya - Fibrianti, Rindhi Dwi; Widya, Moh. Anshori Aris; Utomo, Teguh Priyo (Computech : Jurnal Ilmiah Teknologi Informasi dan Komunikasi, 2024)
The Customer Management Information System (Simapel) of Murni Jaya Internet Service Provider (ISP) is a website to help the management to improve the performance and satisfaction of customers by managing customer data, automating business processes, and providing better services. This research employs data collection methods including observation, interviews, and literature review. The advantages of the system offered increased efficiency and effectiveness, reduced data errors, and cost savings. In the development of the Customer Management Information System (Simapel) of Murni Jaya Internet Service Provider (ISP), the author uses the Waterfall Method as the research approach on its suitability with the system to be developed. The stages in the Waterfall Method begin with identifying system needs, followed by needs analysis, system design, coding, testing, and maintenance stages